Weed control and herbicide selectivity in perennial cotton associated with corn and cowpea - Azevedo, Demóstenes Marcos Pedrosa de; Beltrão, Napoleão Esberard de Macêdo (Pesquisa Agropecuaria Brasileira, 2014)
In order to determine the efficiency of several herbicides against weeds and their phytotoxic effects in perennial cotton Gossypium hirsutum, var. marie galante Hutch, cultivated in association with field corn Zea mays L. and cowpea Vigna unguiculata (L.) Walp. a trial was placed at Patos, PB, Brazil, in 1979. The most strong symptoms of phytotoxicity were caused by the treatments diuron and fluometuron, being Vigna unguiculata the most affected among these species. The most efficient broad leave control was obtained by the herbicides diuron, fluometuron and diuron + pendimethalin. The predominant weeds were: Eleusine indica ( L.) Gaertn, Rhynchelytrum roseum (Nees) Stapf et Hubb., Cenchrus echinatus L., Boerhavia diffusa (Rich.) Kuntze, Acanthospermum hispidum D.C. and Ageratum conyzoides L.